Brain structural trajectories over the adult lifespan - Ziegler, Gabriel; Dahnke, Robert; Jäncke, Lutz; Yotter, Rachel Aine; May, Arne; Gaser, Christian (Human brain mapping, 2012)
The aim of this large‐sample cross‐sectional voxel‐based morphometry (VBM) study of anatomical brain data was to investigate linear and nonlinear age‐related trajectories of grey matter volume in the human brain during the adult lifespan. To date, there are only a few structural brain studies investigating local nonlinear aspects at the voxel level, i.e., without using anatomical ROIs as a priori hypothesis. Therefore, we analyzed 547 T1‐weighted MR images of healthy adult brains with an age range of 19 to 86 years, including 161 scans of subjects with ages 60 and older. We found that the gray matter volume in some regions did not linearly decrease over time, but rather exhibited a delayed decline. Nonlinear age trajectories were observed in the medial temporal lobe regions, the basal ganglia, and parts of the cerebellum. Their trajectories indicated a preservation of grey matter volume during the early adult lifespan. Interestingly, we found nonlinear grey matter structural dynamics specifically in parts of the brain that have been extensively discussed in the context of learning and memory. We propose a hypothesis in relation to the functional role of these brain regions that may explain these results. Hum Brain Mapp 33:2377–2389, 2012. © 2011 Wiley Periodicals, Inc.